Pengaruh Sikap Keuangan dan Pendapatan terhadap Perencanaan Keuangan Masa Depan di Kabupaten Langkat - Nurhaliza, Siti; Lubis, Fauzi Arif; Syarvina, Wahyu (Regress: Journal of Economics & Management, 2023)
This article aims to analyze the influence of financial attitudes and income both partially and simultaneously on the future financial planning of the community in Langkat Regency. This research uses quantitative methods with a descriptive and associative approach. The sample for this research is the people of Langkat Regency with a sample size of 100 people. The data is analyzed using SPSS software. The results of the analysis show that the financial mindset of the people of Langkat Regency has a significant impact on their long-term financial planning with a value of t-count = 2.922 and t-table = 1.98472 (t-count > t-table), with a significance level of 0.004 <0, 05.Income has a significant impact on long-term financial planning for the people of Langkat Regency with a t-count = 6.026 and t-table = 1.98472 (t-count > t-table), with a significance level of 0.0005 and 0.0005 respectively. 0.05. The mindset of financial income simultaneously has a significant influence on future financial planning for the people of Langkat Regency with a value of f-count = 43.056 and t-table = 3.09 (t-count > t-table), at a significance level of 0 ,000005. The R-squared value of 0.470 indicates that the relationship between financial prospects and income can be explained by 47% of independent factors related to financial planning.